Kriteria Pemilihan Pemasok Menggunakan Analytical Network Process - Dewi Kurniawati; Henry Yuliando; Kuncoro Harto Widodo (Institute of Research and Community Outreach - Petra Christian University, 2013)
The selection of supplier is a strategic decision in supply chain which increase competitive advantages. Every manufacture needs to have a standard supplier selection that appropriate with the requirement of the company. The aims of this paper are promoting some criterias of supplier selection and testing whether there are differences interests against priority criteria referred to of strata tenure distinct. Weights and priorities of the criteria tested with a method of analytic network process (ANP) are also intended to bring up a relation of mutual influence among the criteria. ANP can be used to help making decision of selection supplier and to manage supply chain performance. This paper shows the criteria that influence are the past perfomance, price, communication systems, and a supplier of professionalism is the priority for the production of the company. In the other hand, the importance of management is the delivery time, consistent quality, price, and number of delivery. The difference in perspective is influenced by the level of interest and different responsibilities. The difference this assessment formed the basis of decision-making and strategic policies of the supply chain according to the condition of the company.